2023
DOI: 10.1101/2023.03.02.530925
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Respiration is essential for aerobic growth ofZymomonas mobilisZM4

Abstract: Zymomonas mobilisis an alpha-proteobacterium that is a promising platform for industrial scale production of biofuels or valuable products due to its efficient ethanol fermentation and low biomass generation.Z. mobilishas also intriguing physiology, sometimes difficult to explain by the rules and strategies commonly observed in other bacteria. One of the most mysterious features ofZ. mobilisis its growth in oxic conditions.Z. mobilisis an aerotolerant bacterium that encodes a complete respiratory electron tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…This should result in a more oxidized steady state of respiratory electron carriers, and hence, in a lower rate of respiratory ROS generation. Such reasoning seems to be in line with the recent findings of Felczak and TerAvest [48]. They reported that, while the decrease in the respiration rate due to the deletion of ndh in the strain ZM4 stimulated aerobic growth, a similar decrease in respiration attained in result of the deletion of cytochrome bd had an opposite effect.…”
Section: Discussionsupporting
confidence: 88%
“…This should result in a more oxidized steady state of respiratory electron carriers, and hence, in a lower rate of respiratory ROS generation. Such reasoning seems to be in line with the recent findings of Felczak and TerAvest [48]. They reported that, while the decrease in the respiration rate due to the deletion of ndh in the strain ZM4 stimulated aerobic growth, a similar decrease in respiration attained in result of the deletion of cytochrome bd had an opposite effect.…”
Section: Discussionsupporting
confidence: 88%
“…4A, Table S9). This discrepancy could be explained by the possibly redundant function of atp with the Z. mobilis aerobic respiratory chain, which has an elusive function but may contribute to proton gradient generation and/or detoxification of oxygen (43,87).…”
Section: Discussionmentioning
confidence: 99%
“…1B); these genes largely encode horizontally-transferred elements (e.g., CRISPR-associated immune systems) and hypothetical proteins (Table S8). Genes carried by other Alphaproteobacteria but not by Z. mobilis are largely related to oxidative phosphorylation (e.g., type I NADH dehydrogenase, cytochrome c oxidase) and some TCA cycle components that are known to be absent in Z. mobilis (Table S8) (41)(42)(43)(44)(45).…”
Section: Z Mobilis Is An Emerging Model For Small-genome Free-living ...mentioning
confidence: 99%